Carboboration of isocyanates with tris(pentafluorophenyl)borane and evidence for dissociative FLP chemistry of an acid–base pair - Mehta, M; Goicoechea, J (Royal Society of Chemistry, 2019)
We report on the reactivity of isocyanates towards tris(pentafluorophenyl)borane which was found to result in the 1,2-carboboration of the isocyanate C=O bond. The resulting six-membered heterocyclic compounds can be rationalized as adducts of imino-boranes with isocyanates and react accordingly, allowing for the dissociative displacement of the trapped isocyanate moiety in a series of exchange reactions. Related carboelementation reactions with the heavier group 13 analogues, Al(C6F5)3 and Ga(C6F5)3, result in a dimerization of the carboboration products to afford eight-membered heterocycles.